Spectrofluorometric determination of ascorbic acid using thiamine and potassium ferricyanide. Issue 3 (4th May 2017) - Duan, Ruilin; Jiang, Junze; Liu, Shaopu; Yang, Jidong; Zhu, Jinghui; Qiao, Man; Yan, Jingjing; Hu, Xiaoli
ABSTRACT: A simple and sensitive spectrofluorometry method for the determination of ascorbic acid was reported. In alkaline solution, the nonfluorescent thiamine was oxidized by potassium ferricyanide and formed the fluorescent thiochrome with an excitation maximum at 367 nm and an emission peak at 441 nm. However, the fluorescence intensity gradually decreased in the presence of ascorbic acid. The decreased fluorescence was linearly dependent under the optimum conditions with the concentration of ascorbic acid from 0.086–1.5 µmol L −1 with a correlation coefficient of 0.9996. The detection limit of 0.026 µmol L −1 was lower than many other methods. Additionally, the mechanism underlying the enhancement and quenching of this method was discussed. The protocol was used to determine ascorbic acid in tablets and juice with satisfactory results.